Mechanical performance of hybrid polymer–lipid vesicles with leaflet asymmetry engineered using microfluidics - Yuting Huang; Arash Manafirad; Simon Matoori; Laura R. Arriaga; Sijie Sun; Anqi Chen; Xin Yang; Anthony D. Dinsmore; David J. Mooney; David A. Weitz (Proceedings of the National Academy of Sciences, 2026)
Lipid vesicles consist of aqueous cores surrounded by a bilayer of phospholipids. Hybrid polymer–lipid vesicles incorporate both polymers and lipids, offering promising properties for developing pharmaceuticals, biosensors, and artificial cells. The hybrid vesicles can be symmetric, with two leaflets of identical compositions, or asymmetric, in with leaflets of dissimilar compositions, which can lead to dramatically altered properties. However, existing methods for producing symmetric and asymmetric hybrid vesicles often result in heterogenous compositions and sizes, making it challenging to quantify the effect of asymmetry and limiting applications. Here, we use a microfluidic approach to produce hybrid vesicles with either symmetric or asymmetric leaflets and precisely engineered compositions. We find that the vesicles with asymmetric leaflets are significantly stiffer and tougher than those with symmetric leaflets; moreover, the lateral diffusivity of lipids is greatly decreased. The structure for improved toughness consists of a stretchable lipid inner leaflet and a fully continuous polymer outer leaflet. This approach to precisely engineer asymmetric structures can be applied to hybrid vesicles composed of block copolymers and phospholipids soluble in chloroform and hexane, further expanding their applications.